Comparative genomics and the nature of placozoan species - Eitel, Michael; Francis, Warren R.; Varoqueaux, Frédérique; Daraspe, Jean; Osigus, Hans-Jürgen; Krebs, Stefan; Vargas, Sergio; Blum, Helmut; Williams, Gray A.; Schierwater, Bernd; Wörheide, Gert (PLOS Biology, 2018)
Placozoans are a phylum of nonbilaterian marine animals currently represented by a single described species, Trichoplax adhaerens, Schulze 1883. Placozoans arguably show the simplest animal morphology, which is identical among isolates collected worldwide, despite an apparently sizeable genetic diversity within the phylum. Here, we use a comparative genomics approach for a deeper appreciation of the structure and causes of the deeply diverging lineages in the Placozoa. We generated a high-quality draft genome of the genetic lineage H13 isolated from Hong Kong and compared it to the distantly related T. adhaerens. We uncovered substantial structural differences between the two genomes that point to a deep genomic separation and provide support that adaptation by gene duplication is likely a crucial mechanism in placozoan speciation. We further provide genetic evidence for reproductively isolated species and suggest a genus-level difference of H13 to T. adhaerens, justifying the designation of H13 as a new species, Hoilungia hongkongensis nov. gen., nov. spec., now the second described placozoan species and the first in a new genus. Our multilevel comparative genomics approach is, therefore, likely to prove valuable for species distinctions in other cryptic microscopic animal groups that lack diagnostic morphological characters, such as some nematodes, copepods, rotifers, or mites.